2007
DOI: 10.1080/18811248.2007.9711855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Moisture Content on Radon and Thoron Exhalation

Abstract: ÃÃIn this study, the authors considered the effect of soil moisture in the emanation process of radon and thoron gases. Weathered granite soil was selected as the test soil and it was packed in a polypropylene container (275 Â 210 mm 2 and 100 mm in height), up to 50 mm in depth from the bottom. The container was covered with the exhalation rate measuring instrument adopting the accumulation method and -particles were counted at 30 s intervals for 30 min to estimate the exhalation rates. A sporadic increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 17 publications
2
24
1
Order By: Relevance
“…The saturation value was reached at humidity greater than 5% with one sample, but only at humidity >30 to 40% with the other sample. High humidity close to 100% (moisture content of the samples of about 5%) did not lead to reduced exhalation rates, which is different from the results found for thoron from granitic soil by Hosoda et al (2007).…”
Section: Resultscontrasting
confidence: 93%
“…The saturation value was reached at humidity greater than 5% with one sample, but only at humidity >30 to 40% with the other sample. High humidity close to 100% (moisture content of the samples of about 5%) did not lead to reduced exhalation rates, which is different from the results found for thoron from granitic soil by Hosoda et al (2007).…”
Section: Resultscontrasting
confidence: 93%
“…In this regard, it should be noted that the natural moisture content of soil in Gorny Altai is significantly less than in Tomsk. The maximum RFD values on the soil surface are observed at moisture content from 4% to 7% [8,11]. These moisture values coincide with the natural soil moisture in the Altai Mountains.…”
Section: Resultssupporting
confidence: 64%
“…2. Studies [8][9][10][11] show that soil moisture has a profound effect on RFD measurement results. Therefore, to determine soil natural moisture soil sampling was also carried out by means of the cutting ring method at the selected sites.…”
Section: Figure 1 Layout Of the Radon Flux Density Measurement Sitesmentioning
confidence: 99%
“…On the other hand, moisture content tended to decrease with a distance from the natural radon source, similar to radon concentration. It was reported that the moisture content induced the increasing the radon exhalation rates [21], however when the soil pores were saturated by water, the exhalation rate was decreased due to adsorption of radon onto the solid mineral phase or liquid phase [22]. In this study, the moisture content with very broad range from 20% to 60% was relatively higher than other previous studies because the sampling was conducted after rainy spell.…”
Section: Radon Concentration and Physicochemical Properties Of Soil Smentioning
confidence: 73%